2019
DOI: 10.1097/mpg.0000000000002261
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Eosinophilic Esophagitis in Adolescents With Esophageal Atresia

Abstract: Background and Objective: Eosinophilic esophagitis (EoE) is an increasingly recognized childhood disease. Esophageal atresia (EA) is the most frequent congenital malformation of the esophagus. Recently, cases of EoE occurring in patients with EA have been reported, although the exact prevalence of EoE in EA remains unknown. The aim is to investigate the prevalence of EoE among EA in adolescents and to describe these patients' characteristics. Methods: Systematic upper gastrointestinal endoscopies with multista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Among these, 15 The prevalence of EoE in our cohort of EA survivors (4.0%) was much greater than the 0.1-0.57% estimated in general population, 5 but lower than previously reported (9.5-30%). [11][12][13][14][15][16] Characteristics and main results of previous series are summarized in Table 3. Beside possible regional variability, the main factor accounting for this difference is the approach to esophageal biopsy sampling: "routine" versus "selective".…”
Section: Resultsmentioning
confidence: 99%
“…Among these, 15 The prevalence of EoE in our cohort of EA survivors (4.0%) was much greater than the 0.1-0.57% estimated in general population, 5 but lower than previously reported (9.5-30%). [11][12][13][14][15][16] Characteristics and main results of previous series are summarized in Table 3. Beside possible regional variability, the main factor accounting for this difference is the approach to esophageal biopsy sampling: "routine" versus "selective".…”
Section: Resultsmentioning
confidence: 99%
“…The 55% incidence of reactive airway disease in this study in the EA with EoE cohort was comparable with that reported in literature in EoE patients without EA (44). Atopy was also common in Oliveira (87.5%), Batres's (66%), Gorter's (50%), and Lardenoise study (6, 8, 12). The FIGERS consortium found that 67% of children with EoE had a positive skin prick testing (SPT) to at least one food (14).…”
Section: Clinical Presentationmentioning
confidence: 97%
“…In the same study by Pence et al, they did not find any symptoms which could distinguish between EA patients with EoE from EA patients without EoE or GERD patients, highlighting not only the difficulty of diagnosing EoE based on symptoms alone but also the importance of endoscopy and biopsy for diagnosis of EoE, in the EA cohort, especially in those being considered for fundoplication (42). In a prospective study on 63 adolescents with EA by Lardenois et al chest pain was the only symptom to occur significantly more in EA patients with EoE compared to EA patients without EoE (12).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…EoE is a recognized chronic allergic/ immune condition of the esophagus, characterized by an infiltration of eosinophils in the esophageal mucosa. EoE, whose pathogenesis is unclear, has been reported in several patients following EA/TEF repair (30,70,71), with a prevalence that seems >100-fold higher than in the general population (72). The ESPGHAN-NASPGHAN guidelines recommend ruling out EoE in patients with GER symptoms and refractory to PPI, before proceeding to antireflux (72).…”
Section: Diagnosismentioning
confidence: 99%
“…EoE, whose pathogenesis is unclear, has been reported in several patients following EA/TEF repair (30,70,71), with a prevalence that seems >100-fold higher than in the general population (72). The ESPGHAN-NASPGHAN guidelines recommend ruling out EoE in patients with GER symptoms and refractory to PPI, before proceeding to antireflux (72). For all of those who instead are asymptomatic, the guidelines recommended routine endoscopy throughout childhood, i.e., after stopping PPI therapy, before the age of 10 years, at transition to adulthood (25).…”
Section: Diagnosismentioning
confidence: 99%